The Effect of Knowledge of Entrepreneurship Competency and Stakeholder Support to MSMEs Success - Muliastuti Anggrahini; Dudi Hendaryan (Almana : Jurnal Manajemen dan Bisnis, 2020)
The role of Micro, Small, and Medium Enterprises (MSMEs) in the Indonesian economy has been large since the beginning. The success of MSMEs can be measured by the addition of company assets, increased profits and sales volumes, product advantages and prices, or the addition of company branches, types of products, and the number of employees. The success of MSMEs requires knowledge of entrepreneurial competence and the support of relevant stakeholders. The purpose of this research is to find out and analyze the provision of knowledge about entrepreneurship competence and stakeholder support that can support the success of MSME. This research is a descriptive and verification study with research variables that include knowledge on entrepreneurial competence and stakeholder support for the success of MSMEs. Data were analyzed using path analysis to measure the amount of contribution or influence of independent variables on the dependent variable, both direct and indirect effects through relationships with other independent variables. The analysis results showed that entrepreneurship competency knowledge (t-value = 2.910) and support of stakeholders (t-value 3.658) have a significant impact on the MSMEs’ success (f-value = 18.443). The total effect of knowledge on entrepreneurial competence on the success of MSMEs was valued at 18.9% and the total direct and indirect influence of stakeholder support variables on the success of MSMEs was 25.1%. Keywords: